2022
DOI: 10.3390/agronomy12092008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Rice Yield Estimation Using Multiple Linear Regression Analysis, Semi-Physical Approach and Assimilating SAR Satellite Derived Products with DSSAT Crop Simulation Model

Abstract: Accurate and consistent information on the area and production of field crops is vital for national and state planning and ensuring food security in India. Satellite-based remote sensing offers a suitable and cost-effective technique for regional- and national-scale crop monitoring. The use of remote sensing data for crop yield estimation has been demonstrated using a semi-physical approach with reasonable success. Assimilating remote sensing data with the DSSAT model and spectral indices-based regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The Overall accuracy (> 80 per cent) and kappa score (>0.50) indicated that the assessment was of high quality. The results were in accordance with [28][29][30][31] has delineated the crop area estimation with high classification accuracy using multi temporal sentinel 1A data had indicated the suitability of remote sensing-based products for crop area estimation and monitoring for policy decisions, including crop insurances.…”
Section: Peanut Area and Accuracy Assessmentsupporting
confidence: 87%
“…The Overall accuracy (> 80 per cent) and kappa score (>0.50) indicated that the assessment was of high quality. The results were in accordance with [28][29][30][31] has delineated the crop area estimation with high classification accuracy using multi temporal sentinel 1A data had indicated the suitability of remote sensing-based products for crop area estimation and monitoring for policy decisions, including crop insurances.…”
Section: Peanut Area and Accuracy Assessmentsupporting
confidence: 87%
“…Yield estimation and validation were part of the workflow diagram. Estimation of yield was performed as part of a model generation, where the model was generated using regression analysis, which is shown below [ 40 ]. Further, the methodology for the validation of the obtained yield is also illustrated in Figure 13 below.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed review of various data assimilation methods, widely used remote sensing data, diverse crop models used, and the current status of data assimilation application with crop models can be found in Jin et al (2018) and Huang et al (2019). Such data assimilation applications have included the use of remote sensing data along with crop simulation models to estimate regional evapotranspiration, water-use efficiency, and primary production of wheat and maize in China and rice in India (Pazhanivelan et al, 2022). Data assimilation methods have been used to update LAI and the Normalized Differential Vegetation Index (NDVI) from satellite data to improve simulation of wheat yields under irrigation (Jin et al, 2022).…”
Section: Field-and Regional-level Yield Responsesmentioning
confidence: 99%
“…(2019). Such data assimilation applications have included the use of remote sensing data along with crop simulation models to estimate regional evapotranspiration, water‐use efficiency, and primary production of wheat and maize in China (Wang, Lei, Li, Huo, et al., 2023; Wang, Lei, Li, Qu, et al., 2023) and rice in India (Pazhanivelan et al., 2022). Data assimilation methods have been used to update LAI and the Normalized Differential Vegetation Index (NDVI) from satellite data to improve simulation of wheat yields under irrigation (Jin et al., 2022).…”
Section: Crop Models As Tools In Climate Change Assessmentmentioning
confidence: 99%